Hubungan antara Konformitas Teman Sebaya dengan Prokrastinasi Akademik - Siregar, Ricky; Arisandy, Desy (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2024)
In the world of education, we often find a lot of student behavior that is not good, for example, their behavior often delays doing the assignments given by the teacher. This study aims to determine the relationship between peer conformity and academic procrastination in class VIII students of SMPN 50 Palembang. The hypothesis proposed in this study is that there is a relationship between peer conformity and academic procrastination in class VIII students of SMPN 50 Palembang. The population in this study amounted to 250 students in grade VIII, of which 104 students in grade VIII were used as research samples. The sampling technique used in this study was to use the Isaac and Michael formula. The measuring instruments used in this study are the peer conformity scale and the academic procrastination scale. The results of the analysis of research data with the help of the SPSS version 20 for windows program, showed a correlation coefficient (R) of 0.879 coefficient of determination (R2) of 0.772, and a P value = 0.000 The results of the analysis obtained indicate a very significant relationship between peer conformity and academic procrastination in class VIII students of SMPN 50 Palembang by 77.2%.